HGG-12. PRIMARY BITHALAMIC GLIOMA WITH EGFR MUTATION: A RARE CASE REPORT. Issue 2 (22nd June 2018) - Antony, Reuben; Solomon, David; Jin, Lee-Way; Perry, Arie; Mueller, Sabine; Zwienenberg-Lee, Marike; Ozturk, Arzu
Abstract: BACKGROUND: Primary Bilateral Thalamic Gliomas (PBTG) are rare in children. They usually have high grade infiltrative histology and absence of the histone H3 K27M mutation. Most affected patients have a poor outcome regardless of therapy. We report a 12 year old boy diagnosed with a PBTG harboring an EGFR exon 20 insertion mutation commonly seen in lung adenocarcinoma but very rare in childhood glioma. CASE REPORT: Our patient presented to an outside hospital (OSH) with a 4 day history of worsening bifrontal headaches. CT brain demonstrated an intracranial mass so patient was transferred to our center. MRI brain performed at admission demonstrated large non-enhancing bithalamic masses with mass effect on the third ventricle/Foramina of Monro. Biopsy of the left thalamic mass followed by immunohistochemistry and genomic analysis (targeted next-generation sequencing) resulted in the following integrated diagnosis - high grade (WHO Grade 3) infiltrating glioma, IDH and H3-wildtype, hemizygous TP53 frameshift mutation, focal homozygous deletion of CDKN2A / CDKN2B tumor suppressor genes, and a small in-frame insertion (exon 20) of the EGFR oncogene. The presence of an EGFR exon 20 insertion mutation affecting the intracellular tyrosine kinase domain is exceptional in this tumor. No pathogenic alterations in BRAF, NF1, FGFR1, MET, PTEN, PDGFRA, IDH1/IDH2, H3F3A, HIST1H3B, ATRX, or TERT genes were identified. He completed chemoradiotherapy (irradiation/temozolomide/bevacizumab) and is currently receiving maintenance therapy with bevacizumab, temozolomide, and a CNS penetrating 3rd generation EGFR pathway inhibitor osimertinib. CONCLUSION: Interrogating PBTGs for EGFR mutations may reveal a therapeutic target and improve the outcome of affected patients.